Guidance for percutaneous tracheostomy: ultrasonography, fiberoptic bronchoscopy, or no guidance at all - Ibrahim Fadl Mahmoud; Neazy A Abdelmottaleb; Ahmed M El-Shiekh; Saud M Erwi (Wolters Kluwer Medknow Publications, 2019)
Background Percutaneous tracheostomy is widely practiced in intensive care units. It had lower rate of complications. However, serious adverse events still liable to occur. Guidance is proposed to decrease such events. Aim of the work To examine the effect of ultrasound or bronchoscopy guidance on the clinical outcome and complication rate of percutaneous tracheostomy. Patients and methods Sixty patients were prospectively randomized to underwent bronchoscopy, ultrasound, or combined guidance (20 patients each) and data sheets of 20 patients were retrospectively analyzed. Then clinical outcome and rate of major or minor complications were document. Results Total rate of minor complications was significantly increased in none-guidance group (50.0%) when compared to ultrasound guided (25%) or combined guidance (20%) groups. But the difference was non significant when compared to bronchoscopy-guided group (40.0%). Individually, no complication showed significant difference between any of studied groups. The total procedure time was significantly prolonged in non-guided group when compared to each of guided groups, and in combined-guidance group when compared to other groups. Conclusion The combined guidance by both bronchoscopy and ultrasound was associated with significant reduction of overall complications rate. Ultrasound-guided is superior to bronchoscopy guided although the difference was non-significant.